Amebiasis in Pediatric: A Case Report - Bukhori, Imam; Jodjana, Mikael Stevan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Acute gastroenteritis (AGE) is a leading cause of morbidity and mortality in children under five globally, particularly in resource-limited settings. Amebiasis, caused by Entamoeba histolytica, accounts for 4–10% of pediatric diarrheal cases in endemic regions and is associated with symptoms such as bloody diarrhea, abdominal pain, and fever. Complications like dehydration and electrolyte imbalances require prompt diagnosis and management. This case highlights the clinical presentation, diagnostic challenges, and treatment of amebiasis-induced gastroenteritis in a pediatric patient, emphasizing the importance of timely intervention to prevent severe outcomes. Presented is the case of a 6-year-old child who was brought by his mother with complaints of liquid defecation since yesterday morning accompanied by fever, abdominal pain, nausea, and vomiting. Vital signs showed tachycardia, tachypnea, and increased body temperature (38°C). The patient’s nutritional status was found to be of good weight with normal stature. On general examination, it was found that both lower eyelids looked sunken, the lips were dry, and skin turgor was slowed down. There is epigastric tenderness VAS 6/10. Laboratory examination revealed a decrease in erythrocyte index and hyponatremia. On macroscopic examination of complete feces, mucus was found without blood. Microscopically, amoebic histolytic cysts were found, increased leukocytes (20-25/field of view), and erythrocytes (10-15/field of view). Plain abdominal radiograph examination concluded that the shadow of normal intestinal gas was mixed with prominent fecal material.